Sources of gains in horizontal mergers: evidence from customer, supplier, and rival firms - Fee, C.Edward; Thomas, Shawn (Journal of Financial Economics, 2004)
We investigate the upstream and downstream product-market effects of a large sample of horizontal mergers and acquisitions from 1980 to 1997. We construct a data set that identifies the corporate customers, suppliers, and rivals of the firms initiating horizontal mergers and use this data set to examine announcement-related stock market revaluations and post-merger changes in operating performance. We find little evidence consistent with increased monopolistic collusion. However, we do find evidence consistent with improved productive efficiency and buying power as sources of gains to horizontal mergers. The nature of the buying power gains, i.e., rents from monopsonistic collusion or improved purchasing efficiency, is also investigated.